Computational Thinking and Scientific Modules: Effectiveness on Students' Cognitive Learning Outcomes and Critical Thinking Skills - Safitri, Silvia Yuni; Suharno, Suharno; Fauzi, Ahmad (Jurnal Materi dan Pembelajaran Fisika, 2024)
The purpose of the research is to find out whether or not 1) there were different effects using learning modules with Computational Thinking (CT) and scientific approaches, 2) different effects on students’ critical thinking ability in the high and low categories, 3) interaction between the effects using learning modules with CT and scientific approaches in the level of students’ critical thinking ability on cognitive learning outcomes in temperature and heat subject. This research method was quasi-experimental with a quantitative approach. The design used a non-equivalent post-test-only control group design and a 2x2 factorial design pattern.  The population was students of XI MIPA SMA Negeri 1 Kartasura in the academic year of 2021/2022. The sample was chosen using a cluster random sampling technique. Two classes were used as the samples: 36 students of XI MIPA 2 as the first experiment class and 36 students of XI MIPA 4 as the second experiment class—the data collecting technique used documentation, test, and questionnaire techniques. Data were analyzed using non-parametric test statistics, and the method was the Mann-Whitney test. The conclusions of the research results are: 1) there are no effects of using learning modules with CT and scientific approaches on cognitive learning outcomes, 2) there are no effects on student’s critical thinking ability in the high and low categories towards cognitive learning outcomes, 3) there is no interaction between the effects of using learning modules and students’ critical thinking ability on cognitive learning outcomes in temperature and heat subject. This study shows the effectiveness of applying learning modules with CT and scientific approaches to students' critical thinking skills on cognitive learning outcomes on Temperature and Heat material.